2020
DOI: 10.1088/1757-899x/785/1/012048
|View full text |Cite
|
Sign up to set email alerts
|

Research reactor operator performance based on the human error assessment and reduction technique (HEART)

Abstract: This study is an attempt to apply the Human Error Assessment and Reduction Technique (HEART) method in order to quantify the human failure event (HFE) for probabilistic safety assessment (PSA) of a TRIGA Mark II reactor, situated at the Malaysia Nuclear Agency, Malaysia. This serves the qualitative part of the human reliability analysis (HRA) framework and HEART method is considered due to its potential applicability in quantifying human error probability (HEP) for other industries, beside nuclear power. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…menggunakan Metode HEART untuk menganalisis kesalahan yang dilakukan manusia di tenaga nuklir. Hasil dari penelitian mereka akan diterapkan dalam kualifikasi frekuensi keadaan akhir urutan kejadian pada probabilistic safety assessment (PSA) (Hassan et al, 2020). Pengukuran tingkat keandalan operator dengan menggunakan HEART juga telah dilakukan Y S Rejeki et.al.…”
Section: Pendahuluanunclassified
“…menggunakan Metode HEART untuk menganalisis kesalahan yang dilakukan manusia di tenaga nuklir. Hasil dari penelitian mereka akan diterapkan dalam kualifikasi frekuensi keadaan akhir urutan kejadian pada probabilistic safety assessment (PSA) (Hassan et al, 2020). Pengukuran tingkat keandalan operator dengan menggunakan HEART juga telah dilakukan Y S Rejeki et.al.…”
Section: Pendahuluanunclassified
“…A series of studies have been undertaken to determine the initial possibility of a failure occurring. Current research involves the study of human error in the marine industry as the cause of marine accidents [3]; maintenance operations in the marine industry [4]; calculation of human error that will cause specific grounding events [5]; the evaluation of human error in railway accidents [6,7]; human-induced actions with the potential to expose operators working in a radiation-emitting facility to radiation [8,9]; human error during the steam boiler operation [10,11]; and the human error probability in a probability security assessment of the reactor in nuclear power plants [12]. Research has Sustainability 2022, 14, 10838 2 of 16 demonstrated that the human factor is an important risk factor in an industry, regardless of production and process.…”
Section: Introductionmentioning
confidence: 99%
“…using the HEART Method to analyze human errors in nuclear power. The results of their research will be applied in qualifying the frequency of the end state of the sequence of events in the probabilistic safety assessment (PSA) (Hassan et al, 2020). Measurement of operator reliability using HEART has also been carried out by Y S Rejeki et.al.…”
Section: Introductionmentioning
confidence: 99%